2016
DOI: 10.1007/s00586-016-4879-4
|View full text |Cite
|
Sign up to set email alerts
|

The transitional vertebra and sacroiliac joint dysfunction association

Abstract: Sacroiliac joint dysfunction must be considered when investigating the etiology of low back pain. Particular sensitivity must be exhibited on this subject in patients with transitional vertebrae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…While the exact mechanism is not understood, many studies have suggested that pain may be related to degeneration of the adjacent disc segments and facet joints due to hypermobility and increased forces at the level just cephalad to the transitional segment. 12,16,21,22 As described previously, Mahato 18 demonstrated numerous ways in which LSTV affects the load-bearing mechanics of the lumbosacral spine and contributes to mechan-ical LBP, including hypolordosis associated with L5-S1 fusion and hyperlordosis associated with L5-S1 articulation. Farshad-Amacker et al 23 demonstrated a protective effect for the disc at the transitional segment and increased degenerative changes at the adjacent cephalad disc, particularly for Castellvi-Chan types III and IV LSTV.…”
Section: Classification and Prevalencementioning
confidence: 90%
See 2 more Smart Citations
“…While the exact mechanism is not understood, many studies have suggested that pain may be related to degeneration of the adjacent disc segments and facet joints due to hypermobility and increased forces at the level just cephalad to the transitional segment. 12,16,21,22 As described previously, Mahato 18 demonstrated numerous ways in which LSTV affects the load-bearing mechanics of the lumbosacral spine and contributes to mechan-ical LBP, including hypolordosis associated with L5-S1 fusion and hyperlordosis associated with L5-S1 articulation. Farshad-Amacker et al 23 demonstrated a protective effect for the disc at the transitional segment and increased degenerative changes at the adjacent cephalad disc, particularly for Castellvi-Chan types III and IV LSTV.…”
Section: Classification and Prevalencementioning
confidence: 90%
“…The prevalence of LSTV in the general population varies significantly in the literature, ranging from 4% to 35.6% in the spine literature. 2,4,8,[10][11][12][13][14][15][16] Nardo et al 14 evaluated radiographs of 4636 participants and determined the overall prevalence of LSTV to be 18.1%, with types I and II comprising nearly 80% of LST. The authors also found a significantly higher rate in men compared to women (28.1% vs 11.1%).…”
Section: Classification and Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…It is rare to find reports that discuss the screw insertion anatomy in the context of the variability of sacral morphology seen in transitional lumbosacral variations. 1,34,35 LSTV anatomy in the setting of sacroiliac joint instrumentations can hardly be overemphasized given the variations presented in the sacral anatomy and the vicinity of vital neurovascular structures along the trajectory of screw placement through the upper osseous corridors in the sacrum. This study presents a detailed report on quantitative assessment of LSTV-related sacral anatomy and, at the same time, identifies and compares differences in dimensions between the normal sacrum and those that are associated with lumbosacral transitional subtypes in context of sacroiliac screw insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Lumbosakral GV'nin kronik bel ağrısı, sinir kökü semptomları ve sakroiliak disfonksiyon ile ilişkili olduğu bilinmektedir (7)(8)(9)(10). Bunun yanında GV'nin belirlenmesi ve numaralandırılması özellikle cerrahi öncesi planlamada yanlış seviyelerin cerrahi girişiminden kaçınmak için çok önemlidir.…”
Section: Lumbosakral Geçiş Vertebrasının Numaralandırılmasında Paraspunclassified